Governance capacity and regulatory enforcement: street-level organizations in Beijing's food safety reform. (June 2021) - Yee, Wai-Hang; Liu, Peng
How street-level organizations enforce regulations carries important governance implications. Through reviewing the regulatory enforcement literature and categorizing it into three broad governance modes, this article discusses the individual and organizational capacity prerequisites for street-level organizations to enact the corresponding government–society relationship and improve governance outcomes. Through analyzing enforcement challenges faced by street-level officers in Beijing's recent food safety reform, the article also identifies the essential capacities for street-level organizations to regulate under a legal-hierarchical governance mode. The article hopes to inspire further research to uncover specific governance capacity requirements for other administrative organizations under different governance modes. Points for practitioners: Apart from policy effectiveness, government regulators should also sometimes pay attention to their impacts on governance. Despite frontline regulators' discretion, street-level organizations may improve governance outcomes by devising and implementing regulatory enforcement programs and strategies in line with the governance mode the government is engaged in as what they do enacts the specific government–society relationship in the governing process. Administrators in charge of street-level organizations may benefit from cultivating capacities essential to actualizing the respective governance mode. Absence of these capacities is likely to undermine governance effectiveness.